السياحة البيئية ودورها في التنمية السياحية المستدامة بسلطنة عمان - Ahmed Hamood Hamed Al - Qasmi (Universiti Sains Islam Malaysia, 2024)
This study is entitled eco-tourism and its role in sustainable tourism development in the Sultanate of Oman. It focuses on how the Sultanate of Oman enjoys many eco-tourism potential assets which distinguish it from other neighboring countries. However, these important assets have not received the attention and development needs they require. Consequently, the Sultanate has been unable to become a competitive tourist destination in the region and achieve desired sustainable tourism development practices. This study aims to highlight the impact of tourism and, more specifically, eco-tourism and its effects on Oman's national economy It also seeks to evaluate ecotourism assets in the areas of study in the Sultanate and its role in sustainable tourism development. The researcher has adopted two approaches in this study: a deductive theoretical approach based on the books, studies, research and technical reports issued by the concerned tourism authorities, and practical approach making use of qualitative and quantitative research methodologies. The qualitative methodology consisted of a questionnaire answered by 333 participants while the qualitative methodology consisted of interviews with 7 specialists concerned 111th tourism in Oman. The study is divided into 7 chapters Firstly, "the introduction". followed by, "The understanding of tourism and it kinds". "Eco-Tourism, its principle of development and sustainability", "Discussion about Eco-Tourism and its roles in sustainable tourism in the Sultanate of Oman". "Research Methodology", "Analysis and discussion of the study Findings" and finally. "Results and Recommendations". The study reached several findings, most important of which is Oman's interest in having the tourism sector generate economic revenue as well as job opportunities for citizens. The attention to it will contribute significantly to the achievement of sustainable tourism. The study results showed that the elements of eco-tourism, especially in Salalah, are the main reasons which made the sultanate a desirable tourist destination. It combines Green Mountains, desert tourism, marine tourism and biodiversity. Moreover, the study points out that eco-tourism sites require providing the sites with activities and services to be competitive enough as a tourist destination. The study also found out that the infkastructures, laws and incentives in the different regions in Oman are sufficient to attract local and international investors to invest in the tourism field. The study has additionally revealed that the Sultanate needs various types and levels of hotels and accommodations as well as activities and tourism events. The study has resulted in a variety of recommendations, most importantly the need to focus on eco-tourism through amending the tourism laws and the development of discreet strategic plans by all specialists and global consulting firms. It also recommends focusing the support on the activities and services that are related to eco-tourism. Finally, it highlights that it is essential to link governmental support and facilities for tourism projects with the economic, social and environmental returns of the projects to the goverment as well as society. This may be achieved by developing small and medium-sized enterprises in tourism for their ability to providing job opportunities.